The diamond and the boy : the creation of diamonds & the life of H. Tracy Hall - Holt, Hannah (Balzer + Bray, an Imprint of HarperCollinsPublishers, 2018)
"Before a diamond is a gem, it's a common gray rock called graphite. Through an intense trial of heat and pressure, it changes into one of the most valuable stones in the world. Before Tracy Hall was an inventor, he was a boy--born into poverty, bullied by peers, forced to work at an early age. However, through education and experimentation, he became one of the brightest innovators of the twentieth century, eventually building a revolutionary machine that makes diamonds. From debut author Hannah Holt--the granddaughter of Tracy Hall--and illustrator Jay Fleck comes this fascinating in-depth portrait of both rock and man." -- Publisher annotation.